Performance Analysis of Fisheries Processing Product Group of Government in Bulukumba Regency - Normawati, Sitti; Fachry, Mardiana Ethrawaty; Adhawati, Sri Suro (International Journal of Environment, Agriculture and Biotechnology, 2019)
The purpose of this study was to identify the performance of a group of fisheries processing companies assisted by the government, in this case, the Department of Marine and Fisheries, namely to look at the input performance of production volume and execution of product sales output. This research was conducted for three months from November 2018 to February 2019 in Bulukumba Regency. The method used is descriptive research using qualitative and quantitative approaches. The data taken is primary and secondary data using interview and observation methods. The results of the performance efficiency test of the marine and fisheries service assisted groups are quite efficient.